Intermolecular Formation of Two C−C Bonds across Olefins Enabled by Boron‐Based Relay Strategies. Issue 33 (30th June 2017) - Hidasová, Denisa; Jahn, Ullrich
Abstract : Smooth handoff in the relay : Vinyl boronates enable the direct addition of nucleophilic and electrophilic or nucleophilic and radical‐generating carbon reagents across the double bond with retention of the valuable boronate group. The key to the success of this difficult twofold C−C bond‐formation strategy is the initial relay of the nucleophilic addition to boron and the rearrangement of a 1, 2‐metalate rearrangement, shuttling it to the carbon atom.